Risk of Non-infectious Uveitis with Metformin Therapy in a Large Healthcare Claims Database. (18th August 2022) - Sobrin, Lucia; Yu, Yinxi; Han, Samuel; Susarla, Gayatri; Kempen, John H.; Hubbard, Rebecca A.; VanderBeek, Brian L.
ABSTRACT: Purpose: To determine if metformin is associated with noninfectious uveitis (NIU). Methods: Patients in an insurance claims database who initiated metformin (n = 359, 139) or other oral anti-diabetic medications (n = 162, 847) were followed for NIU development. Both cohort and case-control analyses were performed to assess differing exposure lengths using Cox and conditional logistic regression, respectively. Results: The hazard ratio (HR) for incident NIU was not significantly different between the metformin and non-metformin cohorts [HR = 1.19, 95% Confidence Interval (CI): 0.92–1.54, P = .19]. The case control analysis similarly showed no association between any metformin use 2 years before the outcome date and NIU [odds ratio (OR) = 0.64, 95% CI: 0.39–1.04, P = .07]. However, there was a protective 20 association between cumulative metformin duration [(445–729 days) adjusted OR (aOR) = 0.49, 95% CI: 0.27–0.90, P = .02] and dosage (>390, 000 mg aOR = 0.44, 95% CI: 0.25–0.78, P = .001) compared with no metformin use. Conclusions: Our results suggest metformin use for longer durations may be protective of NIU onset.